The effect of neural pre-stimulus oscillations on post-stimulus auditory ERPs in disorders of consciousness - Lindenbaum, Laura; Steppacher, Inga; Mehlmann, Alexandra; Kissler, Johanna Maria (Frontiers in Neuroscience, 2025)
ObjectivePre-stimulus oscillations predispose subsequent stimulus detection, but the connection between the pre-stimulus EEG activity and post-stimulus event-related potentials (ERPs) has rarely been examined in people in a disorder of consciousness (DoC). Hence, we investigate how pre-stimulus EEG band power is related to post-stimulus ERPs in individual DoC patients.MethodsWe conducted an active auditory oddball paradigm encompassing standard, target and unexpected oddball stimuli with 14 DoC patients (N = 12 minimally conscious state [MCS], N = 2 unresponsive wakefulness syndrome [UWS]). We extracted post-stimulus ERPs as well as pre-stimulus power-spectra.ResultsP3-like differences between brain responses to auditory stimuli were found in seven patients (50%). Delta and theta bands pre-dominated in all patients’ pre-stimulus frequency spectra but patients with significant post-stimulus P3 had on average more pre-stimulus beta and gamma power than those without P3 effects. Pre-stimulus power and post-stimulus ERPs correlated in five patients (36%). Several patients showed negative correlations between pre-stimulus gamma and beta power and post-stimulus ERP variables, suggesting a u-shaped relationship between pre-stimulus high-frequency activity and post-stimulus ERP. Only one patient showed a relationship between pre-stimulus alpha and ERP as previously found in healthy people.ConclusionPre-stimulus frequencies in DoC were related to post-stimulus processing at least in some patients. The pattern of the relationship showed considerable variability underscoring substantial alterations in brain activity among patients with DoC. The comparison with somatosensory results in the same patients emphasizes the need for multi-modal assessment.SignificanceThe high inter-individual variability in the connection between pre-stimulus oscillations and auditory processing in DoC necessitates extensive individual assessment to determine optimal stimulation windows for DoC patients.